Solid electrolyte and preparation method thereof, battery and electric device
By using composite solid electrolytes in lithium-ion batteries, combined with fluorinated covalent organic framework, polyvinyl chloride and polyvinylidene fluoride-hexafluoropropylene copolymer, the problems of insufficient energy density of lithium-ion batteries and the growth of lithium dendrites are solved, and higher battery stability and energy density are achieved.
Patent Information
- Application Number
- CN202510097824.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-21
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2045-01-21
AI Technical Summary
The energy density of existing lithium-ion batteries is insufficient, and the use of lithium negative electrodes with low redox potential is prone to form uneven solid electrolyte mesophases, resulting in problems with lithium dendrites and battery stability.
A composite solid electrolyte is used, which includes a fluorinated covalent organic frame (F-COF) material as the filler, polyvinyl chloride (PVC) as the polymer ion conductor, and polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-HFP) as the mechanical support framework, and the lithium ions solubility and migration ability are improved through specific preparation methods.
It improves the ion conductivity and mechanical properties of lithium-ion batteries, inhibits the generation of dendrites, and improves the cyclic stability and energy density of the batteries.
Smart Images

Figure CN119833745A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of battery technology, and in particular to a solid electrolyte and a preparation method thereof, a battery containing the solid electrolyte, and an electrical device containing the battery. Background Art
[0002] The energy density of existing lithium-ion batteries will reach a bottleneck and cannot meet the energy density requirements of rechargeable batteries in the electric vehicle and grid energy storage industries. Although the use of lithium negative electrodes with low redox potential but high activity can improve energy density, an uneven solid electrolyte interphase (SEI) is formed when metallic lithium contacts the electrolyte, causing loss of active lithium and hindering the uniform deposition of lithium ions, which can easily form lithium dendrites and cause short circuits. In addition, the intrinsic defects of organic electrolytes such as electrolyte leakage, high-pressure decomposition and gas production, and high-temperature volatilization and spontaneous combustion pose high safety risks, and thermal runaway is prone to occur at high temperatures. Using solid electrolytes to replace electrolytes and diaphragms in lithium metal batteries is one of the solutions to inhibit dendrite growth and improve battery stability.
[0003] According to the different material composition and ion transport mechanism, solid electrolytes are divided into inorganic solid electrolytes and polymer solid electrolytes. Compared with polymer solid electrolytes, inorganic solid electrolytes have "point-to-point" contact with the positive and negative electrodes, which increases the interface impedance, and their brittleness makes it difficult to prepare on a large scale, which seriously limits their practicality. However, the existing polymer solid electrolytes have low ion conductivity and still cannot meet practical needs. Summary of the invention
[0004] In view of this, the first aspect of the present application provides a method for preparing a solid electrolyte, comprising: Prepare a filler, comprising: Adding reactants 2,5-dihydroxyterephthalaldehyde and triaminoguanidine hydrochloride into a solvent, mixing, and stirring to react to obtain a reaction product; adding the reaction product into a saturated sodium fluoride aqueous solution and stirring to obtain a product; and The product is washed and dried to obtain a filler; Preparing a mixed slurry, comprising: mixing lithium bis(trifluoromethylsulfonyl)imide, vinylene carbonate, polyvinylidene fluoride-hexafluoropropylene copolymer, the filler and an organic solvent, and then adding an initiator azobisisobutyronitrile to obtain a mixed slurry; and The mixed slurry is dried to obtain a solid electrolyte.
[0005] The method for preparing the solid electrolyte of the embodiment of the present application includes a filler, which is a fluorinated covalent organic framework (F-COF) material, and also includes polyvinyl chloride (PVC) as a polymer ion conductive body, and polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-HFP) as a mechanical support skeleton. The PVC in the solid electrolyte of the embodiment of the present application has abundant -C=O groups that can dissolve a large amount of LiTFSI, which is beneficial to improve the ionic conductivity of the electrolyte. The -C=N and -NH groups in the filler of the F-COF material enable it to promote Li+ dissociation and anchor TFSI – , which is beneficial to increase the lithium ion migration number and further enhance the lithium ion transmission capacity of the polymer solid electrolyte. The F- in the filler is beneficial to construct a stable solid electrolyte interphase (SEI), ensure the uniform and dense deposition of lithium ions on the surface of the negative electrode, and utilize the good mechanical properties of PVDF-HFP to maintain the stable morphology of the electrolyte, thereby inhibiting the formation of dendrites and improving the cycle stability of the battery. The solid electrolyte of the embodiment of the present application combines the characteristics of the polymer electrolyte and the filler, improves the ionic conductivity of the polymer solid electrolyte while giving it better mechanical properties, and promotes the application and development of polymer solid electrolytes.
[0006] In some embodiments, in the step of "adding the reactants 2,5-dihydroxyterephthalaldehyde and triaminoguanidine hydrochloride to a solvent, mixing, and stirring for reaction", the molar ratio of the 2,5-dihydroxyterephthalaldehyde to the triaminoguanidine hydrochloride is (1~1.5):1.
[0007] In some embodiments, in the step of "adding the reactants 2,5-dihydroxyterephthalaldehyde and triaminoguanidine hydrochloride to a solvent, mixing, and stirring for reaction", the solvent includes 1,4-dioxane and deionized water, wherein the volume ratio of 1,4-dioxane to deionized water is (3~5): (1~2).
[0008] In some embodiments, in the step of "washing and drying the product", the drying is vacuum drying, the drying temperature is 90°C to 120°C, and the drying time is 12h to 24h.
[0009] In some embodiments, in the step of "preparing a mixed slurry", the molar concentration of the lithium bis(trifluoromethylsulfonyl)imide in the vinylene carbonate is 0.5-2.0 mol / L, The mass of the polyvinylidene fluoride-hexafluoropropylene copolymer accounts for 15% to 17% of the total mass of the bistrifluoromethylsulfonyl imide lithium, the vinylene carbonate, the polyvinylidene fluoride-hexafluoropropylene copolymer and the filler. The mass of the filler accounts for 0-4% of the total mass of the lithium bis(trifluoromethylsulfonyl)imide, the vinylene carbonate, the polyvinylidene fluoride-hexafluoropropylene copolymer and the filler, and the mass proportion of the filler does not include 0%.
[0010] In some embodiments, in the step of "preparing a mixed slurry", the ratio of the initiator to the vinylene carbonate added is (0.6~1.2) mg:1 mL.
[0011] In some embodiments, in the step of "preparing a mixed slurry", the organic solvent is at least one of acetone, tetrahydrofuran, dimethyl sulfoxide, sulfolane, and N-methylpyrrolidone; The step of "drying the mixed slurry" includes: applying the mixed slurry on a hard plate and letting it stand and keep warm to obtain the solid electrolyte.
[0012] The second aspect of the present application provides a composite solid electrolyte, which is prepared by the preparation method described in the first aspect. The composite solid electrolyte includes a filler, polyvinyl chloride and a polyvinylidene fluoride-hexafluoropropylene copolymer, and the filler is a fluoride of the reaction product of 2,5-dihydroxyterephthalaldehyde and triaminoguanidine hydrochloride.
[0013] A third aspect of the present application provides a battery, comprising a negative electrode sheet, a positive electrode sheet, and the composite solid electrolyte of the second aspect disposed between the positive electrode sheet and the negative electrode sheet.
[0014] A fourth aspect of the present application provides an electrical device, using the battery described in the third aspect as a power source.
[0015] The battery is used as a power source for electronic devices. The battery has stable performance and can stably power the electronic devices. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 The conductivity of the solid electrolyte membranes with different lithium salt concentrations in Comparative Examples 1 to 8.
[0017] Figure 2 The conductivity of the solid electrolyte membrane with different PVDF-HFP addition amounts in Comparative Examples 9 to 11.
[0018] Figure 3 is the conductivity of the solid electrolyte membrane with different COF addition amounts.
[0019] Figure 4It is a comparison chart of the cycle performance of lithium symmetric batteries using the solid electrolyte membranes of Comparative Example 6 and Example 3.
[0020] Figure 5 It is a comparison chart of the cycle performance of lithium metal batteries using the solid electrolyte membranes of Comparative Example 6 and Example 3. DETAILED DESCRIPTION
[0021] In order to more clearly understand the purpose, features and advantages of the present application, the present application is described in detail below in conjunction with the accompanying drawings and specific embodiments. It should be noted that, in the absence of conflict, the embodiments of the present application and the features in the embodiments can be combined with each other. In the following description, many specific details are set forth to facilitate a full understanding of the present application, and the embodiments described are only a part of the embodiments of the present application, rather than all of the embodiments.
[0022] The following will describe some embodiments of the present application in detail with reference to the accompanying drawings. The data range values recorded in the present application shall include the end values unless otherwise specified.
[0023] The embodiment of the present application provides a solid electrolyte and a preparation method thereof. The solid electrolyte includes multiple components and can be called a composite solid electrolyte, which uses a fluorinated covalent organic framework (F-COF) material as a filler, polyvinyl chloride (PVC) as a polymer ion conductive body, and polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-HFP) as a mechanical support skeleton, which can effectively increase the solubility of lithium salts in the composite solid electrolyte to increase its ionic conductivity and improve the lithium ion migration ability.
[0024] The method for preparing the composite solid electrolyte comprises the following steps S1 to S3.
[0025] S1: preparing filler. S1 further includes S11 to S13.
[0026] S11: adding reactants 2,5-dihydroxyterephthalaldehyde and triaminoguanidine hydrochloride to a solvent, mixing, and stirring to react to obtain a reaction product; S12: After the reaction is completed, the reaction product is added to a saturated sodium fluoride aqueous solution and stirred to obtain a product; S13: The product is washed and dried to obtain a filler.
[0027] In step S11, in some embodiments, the molar ratio of 2,5-dihydroxyterephthalaldehyde to triaminoguanidine hydrochloride is (1-1.5): 1. In some embodiments, the solvent includes 1, 4-dioxane and deionized water, wherein the volume ratio of 1, 4-dioxane to deionized water is (3-5): (1-2). In step S11, during the stirring process, argon gas can also be introduced to remove dissolved oxygen in the solution.
[0028] The function of step S12 is to perform ion replacement on the reaction product of 2,5-dihydroxyterephthalaldehyde and triaminoguanidine hydrochloride obtained in step S11 to fluorinate it. In some embodiments, the mass ratio of the saturated sodium fluoride solution to the powder of the reaction product obtained in step S11 is about 4.2%.
[0029] In step S13, anhydrous ethanol can be used for washing.
[0030] The drying in step S13 is vacuum drying, the drying temperature is 90° C. to 120° C., and the drying time is 12 h to 24 h.
[0031] The filler is a fluorinated covalent organic framework (F-COF) material, which is a fluoride of the reaction product of 2,5-dihydroxyterephthalaldehyde and triaminoguanidine hydrochloride.
[0032] S2: preparing a mixed slurry, including: mixing lithium bis(trifluoromethylsulfonyl)imide (LiTFSI), vinylene carbonate (VC), polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-HFP), filler and organic solvent, stirring to make the components uniformly mixed, and then adding an initiator azobisisobutyronitrile (AIBN) to react to obtain a mixed slurry.
[0033] In some embodiments, the molar concentration of LiTFSI dissolved in VC is 0.5-2.0 mol / L. The mass of PVDF-HFP accounts for 15%-17% of the total mass of LiTFSI, vinylene carbonate (VC), polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-HFP) and filler, and the mass of the filler accounts for 0-4 wt% of the total mass of LiTFSI, vinylene carbonate (VC), polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-HFP) and filler. Step S2: Add initiator AIBN and VC in a ratio of 0.6-1.2 mg: 1 mL. Initiator AIBN is a commonly used azo initiator. It is used at 45-65°C, decomposes evenly, and only produces one free radical. The purpose of adding the initiator is to initiate the polymerization of vinylene carbonate (VC) to form polyvinyl carbonate (PVC).
[0034] The organic solvent in step S2 can be at least one of acetone, tetrahydrofuran, dimethyl sulfoxide, sulfolane, and N-methylpyrrolidone.
[0035] After the initiator AIBN is added in step S2, the entire solution system may be heated appropriately to a temperature of 45° C. to 60° C., so that the initiator generates free radicals by thermal decomposition, thereby initiating a polymerization reaction of the vinylene carbonate monomer molecules.
[0036] S3: Drying the mixed slurry to remove the organic solvent to obtain a solid electrolyte.
[0037] In some embodiments, step S3 includes applying the mixed slurry to a smooth hard plate, allowing it to stand, heat-insulate, and dry to obtain a composite solid electrolyte. The heat-insulating temperature is 50-70°C, and the heat-insulating time is 8-16 hours. In step S3, a film-like solid electrolyte of a certain thickness can be obtained by controlling the amount of the mixed slurry applied to the hard plate.
[0038] In some embodiments, the thickness of the solid electrolyte is 5-100 μm. The thickness of the solid electrolyte may be in the range of 5-20 μm, 20-40 μm, 40-60 μm, 60-80 μm or 80-100 μm.
[0039] The present application also provides a composite solid electrolyte obtained by the above preparation method. The composite solid electrolyte comprises: a fluorinated covalent organic framework (fluoride of the reaction product of 2,5-dihydroxyterephthalaldehyde and triaminoguanidine hydrochloride) as a filler, polyvinyl chloride (PVC) as a polymer ion conductive body, and polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-HFP) as a mechanical support skeleton.
[0040] The PVC in the polymer solid electrolyte of the present application has abundant -C=O groups that can dissolve a large amount of LiTFSI, which is beneficial to improving the ionic conductivity of the electrolyte. The -C=N and -NH groups in the filler can both promote the dissociation of Li+ and anchor TFSI. – , which is beneficial to increase the lithium ion migration number and further enhance the lithium ion transmission capacity of the polymer solid electrolyte.
[0041] The F- in the filler is conducive to the construction of a stable solid electrolyte interphase (SEI), ensuring uniform and dense deposition of lithium ions on the surface of the negative electrode, and utilizing the good mechanical properties of PVDF-HFP to maintain the stable morphology of the electrolyte, thereby inhibiting the formation of dendrites and improving the cycle stability of the battery.
[0042] The composite solid electrolyte of the present application combines the properties of polymer electrolytes and fillers, improves the ionic conductivity of polymer solid electrolytes while giving them better mechanical properties, and promotes the application and development of polymer solid electrolytes.
[0043] The present application also provides a battery, including a negative electrode sheet, a positive electrode sheet, and the composite solid electrolyte disposed between the positive electrode sheet and the negative electrode sheet. The battery may be, for example, a stainless steel symmetrical battery, a lithium metal battery, or a lithium symmetrical battery, but is not limited thereto.
[0044] An embodiment of the present application provides an electrical device that uses the above-mentioned battery as a power source.
[0045] The battery of the present application is not particularly limited in its use, and can be used in any electrical device known in the prior art. For example, the electrical device includes, but is not limited to, a laptop computer, a pen-input computer, a mobile computer, an electronic book player, a portable phone, a portable fax machine, a portable copier, a portable printer, a head-mounted stereo headset, a video recorder, an LCD TV, a portable cleaner, a portable CD player, a mini-disc, a transceiver, an electronic notepad, a calculator, a memory card, a portable recorder, a radio, a backup power supply, a motor, a car, a motorcycle, a power-assisted bicycle, a bicycle, a lighting fixture, a toy, a game console, a clock, an electric tool, a flashlight, a camera, a large household battery, and a lithium-ion capacitor.
[0046] The technical solution of the embodiment of the present application is further explained below through specific examples.
[0047] Comparative Example 1 71.77 mg LiTFSI was added to 0.5 mL VC, and 206.6 mg PVDF-HFP was added to 6 mL acetone and heated and stirred to mix the components evenly. Then the initiator was added at a ratio of AIBN:VC = 1 mg / mL, and the mixed slurry was cast on a PP plate. It was left at room temperature for 15 min to allow the acetone to completely evaporate, and then the PP plate was transferred to a vacuum drying oven at 60 ° C for 12 h. Finally, the obtained polymer electrolyte membrane was cut into 18 mm diameter discs for battery assembly.
[0048] Comparative Example 2 The method is substantially the same as Comparative Example 1, except that the amount of LiTFSI added in Comparative Example 1 is changed to 143.54 mg.
[0049] Comparative Example 3 The method is substantially the same as Comparative Example 1, except that the amount of LiTFSI added in Comparative Example 1 is changed to 251.31 mg.
[0050] Comparative Example 4 The method is substantially the same as Comparative Example 1, except that the amount of LiTFSI added in Comparative Example 1 is changed to 229.66 mg.
[0051] Comparative Example 5 The method is substantially the same as Comparative Example 1, except that the amount of LiTFSI added in Comparative Example 1 is changed to 224.02 mg.
[0052] Comparative Example 6 The method is substantially the same as Comparative Example 1, except that the amount of LiTFSI added in Comparative Example 1 is changed to 258.37 mg.
[0053] Comparative Example 7 The method is substantially the same as Comparative Example 1, except that the amount of LiTFSI added in Comparative Example 1 is changed to 272.72 mg.
[0054] Comparative Example 8 The method is substantially the same as Comparative Example 1, except that the amount of LiTFSI added in Comparative Example 1 is changed to 287.08 mg.
[0055] Comparative Example 9 It is basically the same as Comparative Example 6, except that the amount of PVDF-HFP added in Comparative Example 6 is changed to 171.85 mg.
[0056] Comparative Example 10 It is basically the same as Comparative Example 6, except that the amount of PVDF-HFP added in Comparative Example 6 is changed to 206.6 mg.
[0057] Comparative Example 11 It is basically the same as Comparative Example 6, except that the amount of PVDF-HFP added in Comparative Example 6 is changed to 243.45 mg.
[0058] Example 1 Preparation of fillers for COF materials: 0.45 mmol of reactants 2,5-dihydroxyterephthalaldehyde and 0.3 mmol of triaminoguanidine hydrochloride were mixed and added to a mixed slurry of 5 mL of 1, 4-dioxane and 1.5 mL of deionized water, and argon was introduced while stirring to remove dissolved oxygen in the solution. After the reaction, the product was added to a saturated sodium fluoride aqueous solution and stirred. Finally, the product was washed with anhydrous ethanol and dried at 90 °C for 12 h to obtain the filler. Preparation of composite solid electrolyte membrane: 258.37 mg of LiTFSI was added to 0.5 mL of VC, and added to 6 mL of acetone together with 206.6 mg of PVDF-HFP and 11.56 mg of filler and heated and stirred to mix the components evenly. Subsequently, the initiator was added at a ratio of AIBN:VC=1 mg / mL, and the mixed slurry was cast on a PP plate, and the acetone was completely volatilized at room temperature for 15 min. The PP plate was transferred to a vacuum drying oven at 60 °C for 12 h.
[0059] Example 2 The method is substantially the same as Example 1, except that the amount of filler added in Example 1 is changed to 23.37 mg.
[0060] Example 3 The method is substantially the same as Example 1, except that the amount of filler added in Example 1 is changed to 35.4 mg.
[0061] Example 4 The method is substantially the same as Example 1, except that the amount of filler added in Example 1 is changed to 47.71 mg.
[0062] Application Examples The polymer electrolyte membranes obtained in Examples 1 to 4 and Comparative Examples 1 to 11 were cut into discs with a diameter of 18 mm for later use.
[0063] Assembly method of stainless steel symmetrical battery: The battery was assembled using a φ15.8 mm stainless steel gasket and a composite solid electrolyte membrane in a stacking manner of negative electrode shell-spring-gasket-solid electrolyte membrane-gasket-positive electrode shell.
[0064] Preparation method of positive electrode: LiFePO4 (LFP), conductive carbon and polyvinylidene fluoride (PVDF) are mixed evenly in an N-methylpyrrolidone (NMP) reagent in a mass ratio of 8:1:1, and then the resulting slurry is coated on an aluminum foil, and then vacuum dried and cut to obtain a positive electrode sheet.
[0065] Assembly method of lithium metal battery: The spring pieces and gaskets are clamped and placed on the negative electrode shell of the 2025 type battery shell in sequence. The lithium sheet is placed in the center of the gasket and then the solid electrolyte membrane is placed. The positive electrode sheet prepared by the above method is clamped and placed on the composite solid electrolyte membrane. The positive electrode shell is covered and pressed with a button battery packaging machine.
[0066] Assembly method of lithium symmetric battery: The spring pieces and gaskets are clamped and placed on the negative electrode shell of the 2025 type battery shell in sequence. After placing the lithium sheet in the center of the gasket, the solid electrolyte membrane is placed. Another lithium sheet is clamped and placed on the composite solid electrolyte membrane. The positive electrode shell is covered and pressed with a button battery packaging machine.
[0067] Conductivity test method: The electrochemical impedance spectroscopy (EIS) of the stainless steel symmetrical cell was tested using a Gamry electrochemical workstation. The ionic conductivity was calculated using the formula: σ = L / AR, where L is the thickness of the solid electrolyte, A is the area of the stainless steel sheet, and R is the measured impedance.
[0068] Lithium symmetric battery cycle test method: The lithium symmetric battery was cycled using a BlueDian battery test system at 60°C and 0.1 mA / cm 2 and 0.1 mAh / cm 2 Conditional loop.
[0069] Lithium metal battery cycle test method: The lithium metal battery was cycled using a Blue Power battery testing system at 60°C with a 1C current and a charging voltage of 2.5~4.2 V.
[0070] Application Example 1 The composite solid electrolyte membranes of Comparative Example 6 and Example 3 were assembled into lithium symmetrical batteries in the above manner and placed on an electrochemical platform for electrochemical performance testing.
[0071] Application Example 2 The composite solid electrolyte membranes of Comparative Example 6 and Example 3 were assembled into lithium metal batteries in the above manner and placed on an electrochemical platform for electrochemical performance testing.
[0072] Result analysis: The conductivity test results of the composite solid electrolyte membranes of Comparative Examples 1 to 11 and Examples 1 to 4 at different temperatures are shown in Table 1 below.
[0073] As shown in Table 1 and Figure 1 As shown, by comparing Comparative Examples 1 to 8, when Comparative Example 7 (i.e., adding 272.72 mg LiTFSI, i.e., the concentration of LiTFSI in VC is 1.9 mol / L), the prepared composite solid electrolyte membrane has higher electrical conductivity.
[0074] In Comparative Examples 9 to 11, the concentration of LiTFSI in VC was 1.8 mol / L. Figure 2 As shown, by comparing Comparative Examples 9 to 11, when the concentration of LiTFSI in VC is fixed at 1.8 mol / L, the composite solid electrolyte membrane prepared in Comparative Example 9 (i.e., when the PVDF-HFP content is 15.5%wt%) has a higher electrical conductivity.
[0075] In Comparative Example 6 and Examples 1 to 4, 258.37 mg of LiTFSI was added to 0.5 mL of VC, i.e., the concentration of LiTFSI in VC was the same. Figure 3 As shown, by comparing Comparative Example 6 with Examples 1 to 4, the conductivity of the composite solid electrolyte membrane is greatly improved after the addition of fillers. With the increase of filler content, the ionic conductivity of the composite solid electrolyte first increases and then decreases. When the filler content is 3.0 wt%, the ionic conductivity is the largest.
[0076] Table 1 Figure 4 For a lithium symmetrical battery assembled using the solid electrolytes of Comparative Example 6 and Example 3, at 60°C, the current density was 0.1 mA / cm 2 and a deposition capacity of 0.1 mAh / cm2 The long cycle performance of the battery was improved. The polarization voltage of the battery assembled with the electrolyte of Comparative Example 6 increased significantly after 800 h of cycling. In contrast, the battery assembled with the electrolyte of Example 3 cycled stably with almost unchanged polarization voltage (about 40 mV) within 1500 h. This fully demonstrates that the addition of fillers can improve the battery cycle stability.
[0077] Figure 5 The cycling performance of lithium metal batteries assembled using the solid electrolytes of Comparative Example 6 and Example 3 at 60°C and a current density of 1.0 C. The battery with the electrolyte of Comparative Example 6 quickly experienced severe overcharging due to local micro-short circuits caused by lithium dendrites at a 1C rate cycle; in comparison, the battery with the electrolyte of Example 3 still had a discharge capacity of 113.2 mAh / g even after 550 cycles, showing good electrochemical stability and dendrite suppression ability.
[0078] The improvement of lithium salt solubility in the composite solid electrolyte of the present application is beneficial to improving the ionic conductivity of the electrolyte, and the ion transmission capacity of the polymer solid electrolyte is comprehensively improved by adding COF fillers. In addition, the filler has a positive effect on the formation of the solid electrolyte interphase (SEI) at the negative electrode. The polymer solid electrolyte involved in the present application uses PVDF-HFP as a mechanical support skeleton, which enables it to have excellent ionic conductivity while ensuring its good mechanical properties, thereby improving the interface stability and electrochemical performance of the battery.
[0079] The above implementation modes are only used to illustrate the technical solutions of the present application and are not intended to limit the present application. Although the present application has been described in detail with reference to the above preferred implementation modes, a person skilled in the art should understand that the technical solutions of the present application may be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present application.
Claims
1. A method for preparing a solid electrolyte, characterized in that: include: Prepare a filler, comprising: Adding reactants 2,5-dihydroxyterephthalaldehyde and triaminoguanidine hydrochloride into a solvent, mixing, and stirring to react to obtain a reaction product; adding the reaction product into a saturated sodium fluoride aqueous solution and stirring to obtain a product; and The product is washed and dried to obtain a filler; Preparing a mixed slurry, comprising: mixing lithium bis(trifluoromethylsulfonyl)imide, vinylene carbonate, polyvinylidene fluoride-hexafluoropropylene copolymer, the filler and an organic solvent, and then adding an initiator azobisisobutyronitrile to obtain a mixed slurry; and The mixed slurry is dried to obtain a solid electrolyte.
2. The method for preparing a solid electrolyte according to claim 1, characterized in that: In the step of "adding the reactants 2,5-dihydroxyterephthalaldehyde and triaminoguanidine hydrochloride to a solvent, mixing, and stirring for reaction", the molar ratio of the 2,5-dihydroxyterephthalaldehyde to the triaminoguanidine hydrochloride is (1-1.5):
1.
3. The method for preparing a solid electrolyte according to claim 1, characterized in that: In the step of "adding the reactants 2,5-dihydroxyterephthalaldehyde and triaminoguanidine hydrochloride to a solvent, mixing, and stirring for reaction", the solvent includes 1,4-dioxane and deionized water, wherein the volume ratio of 1,4-dioxane to deionized water is (3-5): (1-2).
4. The method for preparing a solid electrolyte according to claim 1, characterized in that: In the step of "washing and drying the product", the drying is vacuum drying, the drying temperature is 90°C to 120°C, and the drying time is 12h to 24h.
5. The method for preparing a solid electrolyte according to claim 1, characterized in that: In the step of "preparing a mixed slurry", the molar concentration of the lithium bis(trifluoromethylsulfonyl)imide in the vinylene carbonate is 0.5-2.0 mol / L, The mass of the polyvinylidene fluoride-hexafluoropropylene copolymer accounts for 15% to 17% of the total mass of the bistrifluoromethylsulfonyl imide lithium, the vinylene carbonate, the polyvinylidene fluoride-hexafluoropropylene copolymer and the filler. The mass of the filler accounts for 0-4% of the total mass of the lithium bis(trifluoromethylsulfonyl)imide, the vinylene carbonate, the polyvinylidene fluoride-hexafluoropropylene copolymer and the filler, and the mass proportion of the filler does not include 0%.
6. The method for preparing a solid electrolyte according to claim 1, characterized in that: In the step of "preparing a mixed slurry", the ratio of the initiator to the vinylene carbonate added is (0.6-1.2) mg:1 mL.
7. The method for preparing a solid electrolyte according to claim 1, characterized in that: In the step of "preparing a mixed slurry", the organic solvent is at least one of acetone, tetrahydrofuran, dimethyl sulfoxide, sulfolane, and N-methylpyrrolidone; The step of "drying the mixed slurry" includes: applying the mixed slurry on a hard plate and letting it stand and keep warm to obtain the solid electrolyte.
8. A solid electrolyte, characterized in that The solid electrolyte is prepared by the preparation method described in any one of claims 1 to 7, and the solid electrolyte includes filler, polyvinyl chloride and polyvinylidene fluoride-hexafluoropropylene copolymer, and the filler is a fluoride of the reaction product of 2,5-dihydroxyterephthalaldehyde and triaminoguanidine hydrochloride.
9. A battery, comprising a negative electrode sheet and a positive electrode sheet, characterized in that: It also includes a solid electrolyte as described in claim 8 disposed between the positive electrode plate and the negative electrode plate.
10. An electrical device, characterized in that: A battery as claimed in claim 9 is used as a power source.
Citation Information
Patent Citations
Composite solid electrolyte, preparation method thereof and lithium ion battery
CN114204110A
Ionic covalent organic framework with guanidine salt and nitrogen-rich sites, preparation method of ionic covalent organic framework and application of ionic covalent organic framework in adsorption of bivalent copper in wastewater
CN115785363A
Ionic liquid-based cross-linked network structure polymer electrolyte with high ionic conductivity and mechanical property and preparation method of ionic liquid-based cross-linked network structure polymer electrolyte
CN117543073A
COF composite polymer solid electrolyte and preparation and application thereof
CN118263510A
Ternary covalent organic framework modified by perfluoroalkyl chain and sulfonic acid group as well as preparation method and application of ternary covalent organic framework
CN118994510A
Cited By
Solid-state electrolyte filler, preparation method of solid-state electrolyte and solid-state battery
CN120749189A